EKSISTENSI BAHASA ARAB KONTEMPORER - M. Dzikrul Hakim (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2018)
In the present day, it can be seen that the existence Arabic is decreasing, because most peopleprefer to learn languages like English, Korean, Chinese, Japanese and others in part. It isregarded as an International Language that is already popular in the world. It is rare to learnArabic. Nowadays Arabic is considered only an old language that has not been polished inthe eyes of the general public and is seen as a religious language. In fact, Arabic is thelanguage that pioneered the Science